Digitalisasi Peran Mursyid: Kajian Pendidikan dan Sosial Kemasyarakatan Tarekat Qadiriyah di Sulawesi Barat - Muhammad Syibli Sahabuddin; Andi Alimuddin Unde; Iqbal Sultan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
The development of digital technology has transformed models of communication and religious practice, including within the Sufi community. The purpose of this study is to analyze the transformation of the role of the murshid of the Qadiriyah Sufi Order in West Sulawesi within the educational and social spheres in the digital era. This research focuses on how the murshid uses digital media, the implications of this media use for spiritual authority, and its influence on the social cohesion of the congregation. This study utilizes a qualitative approach using communication ethnography methods, using in-depth interviews, participant observation, and digital content analysis. The results show that digitalization has reconstructed the role of the murshid from a traditional guide to a spiritual leader and virtual educator. WhatsApp, Zoom, and YouTube are used as tools for preaching, teaching, and strengthening congregational solidarity. These findings also indicate a shift in congregational preference for concise and practical content. Although concerns remain about the diminished spiritual meaning when direct contact with the murshid becomes less frequent. Therefore, digitalization opens up significant opportunities for the development of technology-based religious education, but still requires balance to ensure the spiritual depth and authority of the Sufi tradition are not lost.